Reducing Your Risk for Diabetes: A Resource Guide - Linda B. Bobroff (EDIS)
The number of people with diabetes is rising at an alarming rate in the U.S., as it is worldwide. Many free resources are available to help people of all backgrounds lead healthier lives and reduce their risk for diabetes. Here are some resources to choose from to help you and your family members begin taking steps to improve your health. This revised 3-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, March 2012.